Gamma-glutamyl carboxylase and its influence on warfarin dose - King, Cristi R.; Deych, Elena; Milligan, Paul; Eby, Charles; Lenzini, Petra; Grice, Gloria; Porche-Sorbet, Rhonda M.; Ridker, Paul M.; Gage, Brian F. (Thrombosis and Haemostasis, 2010)
Via generation of vitamin K-dependent proteins, gamma-glutamyl carboxylase (GGCX) plays a critical role in the vitamin K cycle. Single nucleotide polymorphisms (SNPs) in GGCX, therefore, may affect dosing of the vitamin K antagonist, warfarin. In a multi-centered, cross-sectional study of 985 patients prescribed warfarin therapy, we genotyped for two GGCX SNPs (rs11676382 and rs12714145) and quantified their relationship to therapeutic dose. GGCX rs11676382 was a significant (p=0.03) predictor of residual dosing error and was associated with a 6.1% reduction in warfarin dose (95% CI: 0.6%-11.4%) per G allele. The prevalence was 14.1% in our predominantly (78%) Caucasian cohort, but the overall contribution to dosing accuracy was modest (partial R2 = 0.2%). GGCX rs12714145 was not a significant predictor of therapeutic dose (p = 0.26). GGCX rs11676382 is a statistically significant predictor of warfarin dose, but the clinical relevance is modest. Given the potentially low marginal cost of adding this SNP to existing geno-typing platforms, we have modified our non-profit website (www.WarfarinDosing.org) to accommodate knowledge of this variant.
Keywords: Gamma-glutamyl carboxylase; warfarin; pharmacogenetics; algorithm